Code detection software quality tool of electronic shopping cart based on logic scoring preferences model / Juliana Adzmi - Adzmi, Juliana (2006)
The project title for this thesis is Code Detection Software Quality Tool of Electronic Shopping Cart based on Logic Scoring Preferences Model. This project is to develop Electronic Shopping Cart Code Detection Tool that will detect shopping cart code. This tool only can detect PHP files in e-commerce systems. It is because this project focused the research on the e-commerce PHP website. E-commerce PHP website has been chosen for this project is because PHP is a programming language develop for open source and the more important factor here is recently, many system developers applied PHP to develop their systems including e-commerce systems. Logic Scoring Preferences Model is a model that will be used as a guideline of quality level to be identified and used in the development of this tool. And also that's how the result of code detection will be displayed; according to quality level specified by Logic Scoring Preferences Model (0 = unsatisfactory, 1 = marginal, 2 - satisfactory). To achieve one of these project objectives that are to identify the shopping cart characteristics, data collection has been made such as e-commerce websites observation and comparison. This type of data collection has been used to identify the characteristics normally used in e-commerce website arid to identify the differences of characteristics applied by e-commerce websites. Some interviews with e-commerce expertise also have been conducted in order to gain more information for this project. PHP code review on source code of several open source e-commerce website also have been made to achieve thesecond objective of this project which is to identify the PHP source code of electronic shopping cart on e-commerce website. The third and the last objectives of this research were achieved by designing and developing this Electronic Shopping Cart Code Detection Tool